Determinant Influencing Factors For Customer Preferences In Local Fragrance Product (Case Study: Multitude Fragrance) - Yudha Ginting, Pascal; Dellyana, Dina (Cv. Syntax Corporation Indonesia, 2023)
Significant changes have occurred in Indonesian business lines, including the types of local perfume businesses in Indonesia. Even today, Indonesia is one of the world's leading producers and consumers of perfume. According to the Indonesian Perfume Industry Association, Indonesia became Southeast Asia's second largest perfume market in 2019. (AIPI). In recent years, the use of perfume products has increased rapidly in Indonesia, particularly for native perfume items. Technological advancements that make it easier to produce and market regional perfume goods have aided the growth of Indonesia's local perfume sector. Local perfume manufacturers can use technology to improve product quality, streamline production, and simplify marketing and promotion. consumers This study seeks to determine the factors that influence consumers before they decide to purchase a local perfume product. After identifying the factors that influence these preferences, researchers use the AHP (Analytical Hierarchy Process) method to determine the priority of each of these criteria. The researcher also attempted to categorize this research based on five main criteria that were generated based on the experiences of perfume users, namely price, aroma, design quality, marketing promotions, and influence from others. The qualitative analysis method, which was presented descriptively from the results of interviews, and qualitative analysis, which was analyzed using the AHP method and surveys in general, were used by researchers. The results of the AHP analysis are used to influence the purchase of local perfumes after they have been evaluated. This study was carried out for Multitude Fragrance, a local perfume company in Jakarta, Indonesia. The proposed solution is based on the findings of AHP and interviews, and it attempts to address the issues identified in each factor that influences customer preference in selecting local perfume products.